Arquitetura urbana do café em Muqui-ES - Hautequestt Filho, Genildo Coelho (2011)
This paper aims at studying the typology, materials and construction techniques of the urban architecture of the coffee produced in Muqui city, southern state of Espirito Santo, between 1918 (the end of World War I) and 1976 (after the Eradication Program